Efficacy and Safety of Individual Second-Generation vs First-Generation Antipsychotics in First Episode Psychosis: A Systematic Review and Meta-analysis - Zhang, Jian-Ping (2012)
Because early treatment choice is critical in first episode schizophrenia-spectrum disorders (FES), this meta-analysis compared efficacy and tolerability of individual second-generation antipsychotics (SGAs) with first-generation antipsychotics (FGAs) in FES. We conducted systematic literature search (until 12/31/2010) and meta-analysis of acute, randomized trials with ≥1 FGA vs. SGA comparison; patients in their first episode of psychosis and diagnosed with schizophrenia-spectrum disorders; available data for psychopathology change, treatment response, treatment discontinuation, adverse effects, or cognition. Across 13 trials (n=2,509), olanzapine (7 trials) and amisulpride (1 trial) outperformed FGAs (haloperidol: 9/13 trials) in 9/13 and 8/13 efficacy outcomes, respectively, risperidone (8 trials) in 4/13, quetiapine (1 trial) in 3/13, and clozapine (2 trials) and ziprasidone (1 trial) in 1/13, each. Compared to FGAs, EPS-related outcomes were less frequent with olanzapine, risperidone and clozapine, but weight gain was greater with clozapine, olanzapine and risperidone. Pooled SGAs were similar to FGAs regarding total psychopathology change, depression, treatment response, and metabolic changes. SGAs significantly outperformed FGAs regarding lower treatment discontinuation, irrespective of cause, negative symptoms, global cognition, and less EPS and akathisia, while SGAs increased weight more (p’s<0.05-0.01). Results were not affected by FGA dose or publication bias, but industry-sponsored studies favored SGAs more than federally funded studies. To summarize, in FES, olanzapine, amisulpride and, less so, risperidone and quetiapine showed superior efficacy, greater treatment persistence and less EPS than FGAs. However, weight increase with olanzapine, risperidone and clozapine and metabolic changes with olanzapine were greater. Additional FES studies including broader-based SGAs and FGAs are needed.